Cenozoic changes in atmospheric lead recorded in central Pacific ferromanganese crusts - Klemm, V; Reynolds, B; Frank, M; Pettke, T; Halliday, A (2007)
The possible sources of pre-anthropogenic Pb contributed to the world's oceans have been the focus of considerable study. The role of eolian dust versus riverine inputs has been of particular interest. With better calibration of isotopic records from central Pacific ferromanganese crusts using Os isotope stratigraphy it now appears that deep water Pb isotopic compositions were effectively homogeneous over a distance of 5000 km for the past 80 Myr. The composition shifted slightly from high 206Pb/204Pb ratios in the range of 18.87 ± 0.02 before 65 Ma to lower values of 18.62 ± 0.02 by 45 Ma and then gradually increased again very slightly to the present day ratio of 18.67 ± 0.02. The regional homogeneity provides evidence of a dominant well-mixed atmospheric source the most likely candidate for which is volcanic aerosols contributed either directly or as soluble condensates on eolian dust. The slight shift in Pb isotope composition of deep waters in the central Pacific between 65 and 45 Ma may be the result of a regional- or perhaps global-scale change in the sources of volcanic exhalations and volcanic activity caused by an increase in the importance of melting and assimilation of older continental crustal components over the Cenozoic. © 2006 Elsevier B.V. All rights reserved.